Job Satisfaction In Automobile Sector During Economic Recession – With Special Reference to Two-Wheeler Industry In India: Analyzing the Impact of Recession on Job Satisfaction in the Automobile Sector (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the currentcompetitive environment, human resources management is a complex activity thatdetermines, to a large extent, the organizational effectiveness. The mainpurpose of this article is to analyze attitudes of staff towards their job incase of economic recession; many financial rewardsmainly generate short-term boosts of energy, which can have damaging unintendedconsequences. Indeed, the economic crisis, with its imperative to reduce costsand to balance short- and long-term performance effectively, gives businessleaders a great opportunity to reassess the combination of financial andnonfinancial incentives that will serve their companies best through and beyondthe downturn. As industry moves forward in deploying lean concepts, it isimportant to recognize the potential benefit for attacking waste inabove-the-shop-floor processes. This paper attempts to analyze the impact thatrecession has on motivation and job satisfaction level of employees Inautomobile sector as well as the attempts made by organizations to keepemployees satisfied and retain the best talent in troubled times.